Hicks in HANK: Fiscal responses to an energy shock - Christian Bayer; Alexander Kriwoluzky; Gernot J. Müller; Fabian Seyrich (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
The distributional and disruptive effects of energy supply shocks are potentially large. We study the effectiveness of alternative fiscal responses in a two-country HANK model that we calibrate to the euro area. Energy subsidies can stabilize the domestic economy, but are fiscally costly and generate adverse spillovers to the rest of the monetary union: What the subsidizing country gains, the other countries lose. Transfers based on historical energy consumption in the form of a Hicks/Slutsky compensation are less effective domestically as subsidies but do not harm economic activity abroad. In addition, transfers increase welfare at Home while subsidies reduce welfare.
Keywords: D31; E64; F45; Q41; 330; Energy crisis; Subsidies; Transfers; HANK 2; monetary union; spillovers; heterogeneity; inequality; households